Distinct different sensitivity of Treg and Th17 cells to Fas-mediated apoptosis signaling in patients with acute coronary syndrome - Li, Qing (e-Century Publishing Corporation, 2013)
Objective: An imbalance in CD4(+)CD25(+) regulatory T (Treg) cells and Th17 cells has been found to correlate to occurrence of acute coronary syndrome [ACS, including unstable angina (UA) and acute myocardial infarction (AMI)]. However, the mechanisms of Th17/Treg imbalance in ACS patients are still unclear. The purpose of this study is to investigate the possibility of differences in sensitivity of Th17 and Tregs to Fas-mediated apoptosis which could lead to Th17/Treg imbalance in ACS patients. Methods: We examined the apoptosis of Th17 and Treg cells, apoptosis-related Fas/Fas ligand(FasL) pathway, and inflammatory markers in patients with AMI, UA, stable angina (SA) and controls by Flow cytometry and ELISA. Then we analysed the correlation of inflammatory markers and sFasL to Treg apoptosis, and the effect of anti-FasL antibody on Treg apoptois in vitro. Results: Our study demonstrated that apoptotic Tregs, Fas and FasL expression, Caspase-3 activity of Tregs were significantly higher in ACS patients than those in NCA and SA patients (all P < 0.05). The percentage of apoptotic Tregs is positively correlated with the levels of inflammatory markers and sFasL. In vitro incubation of peripheral blood mononuclear cells from ACS patients with anti-FasL antibody resulted in a markedly reduction of apoptotic Treg cells. However, there were no significant differences in apoptotic Th17 cells and in Fas and FasL expression for Th17 cells between the four groups (all P >0.05). Conclusions: Tregs, but not Th17 cells, become apoptotic through Fas/FasL pathway, which contributed to reduction of Tregs leading to an imbalance between Th17 and Treg cells. This could be the mechanism underlying Th17/Treg imbalance and occurrence of ACS.